ANALISIS HUBUNGAN KOMPENSASI DENGAN KINERJA PEGAWAI (Studi Pada UPT. Laboratorium Konstruksi dan UPR Jalan dan Alat Berat Dinas Pekerjaan Umum Kabupaten Kutai Timur) - Nasrudin, Nasrudin (PREDIKSI, 2016)
This study aims to determine the compensation systems and employee performance as well as the correlation between compensation and employee performance UPT. Laboratory Construction and Heavy Equipment UPR Roads and Public Works Department of East Kutai. The method used in this research is quantitative descriptive approach. The results of this study indicate that the value of Spearman rank correlation coefficient (rs) = 0.333. The result of this calculation is greater than the critical value of the prices in the table Spearman rank correlation coefficient, for n = 36 at a significance level of 5%, that is equal to 0.329. This means that there is a correlation or a positive and significant relationship between variable compensation with performance variables. The results also showed that R-Square is generated is equal to 0.111. This means that the variable compensation accounted for 11.1% of the gains generated by employees of UPT. Laboratory Construction and Heavy Equipment UPR Roads and Public Works Department of East Kutai. Or in other words that there is a positive and significant relationship between compensation and employee performance UPT. Laboratory Construction and Heavy Equipment UPR Roads and Public Works Department of East Kutai. Thus, the hypothesis formulated in this study can be received and verified.Â span>Â Â